KMTNet Nearby Galaxy Survey: Overview and Survey Description. (1st September 2022) - Byun, Woowon; Sheen, Yun-Kyeong; Seon, Kwang-Il; Ho, Luis C.; Lee, Joon Hyeop; Jeong, Hyunjin; Kim, Sang Chul; Park, Byeong-Gon; Lee, Yongseok; Cha, Sang-Mok; Kim, Minjin
Abstract: Recently, there has been increasing demand for deep imaging surveys to investigate the history of the mass assembly of galaxies in detail by examining the remnants of mergers and accretions, both of which have very low surface brightness (LSB). In addition, the nature of star formation in LSB regions, such as galaxy outer disks, is also an intriguing topic in terms of understanding the physical mechanisms of disk evolution. To address these issues, this study conducted a survey project, called the Korea Microlensing Telescope Network Nearby Galaxy Survey, to construct a deep imaging data set of nearby galaxies in the southern hemisphere. It provides deep and wide-field images with a field of view of ∼12 deg 2 for 13 nearby galaxies drawn from the Carnegie–Irvine Galaxy Survey catalog in optical broad bands ( BRI ) and an H α narrow band. Through a dedicated data reduction, the surface brightness limit in 10″ × 10″ boxes was found to reach as deep as μ 1 σ ∼ 29–31 mag arcsec −2 in the optical broad bands and f 1 σ ∼ 1–2 × 10 −18 erg s −1 cm −2 arcsec −2 in the H α narrow band. To conclude the paper, several possible scientific applications for this data set are described.